Negotiating Identity Through Language: A Linguistic Landscape Analysis of Islamic Boarding School Names in Malang, Indonesia - Very Erawanto; Nudya Kuntum Khoirel Abidah; Rosyidatul Hikmawati; Muhammad Farih (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
The linguistic landscape of Islamic boarding schools offers insight into the ways educational institutions express religious values and cultural affiliations through language. This study explores how pesantren in Malang, Indonesia, construct and negotiate their identities through institutional naming practices displayed in public spaces. Adopting a qualitative descriptive approach, the research involved twenty-nine Islamic boarding schools selected purposively to represent different institutional backgrounds. Data were gathered through direct observation, photographic documentation, and semi-structured interviews and subsequently analyzed using Sudaryanto’s correspondence method and thematic analysis. The findings identify four linguistic patterns in pesantren names: monolingual Javanese, bilingual Indonesian–Javanese, bilingual Javanese–Arabic, and multilingual Indonesian–Javanese–Arabic forms. The predominance of the Javanese–Arabic pattern indicates a close connection between local cultural traditions and the symbolic authority of Islam. While Arabic serves to reinforce religious legitimacy, Indonesian facilitates broader social communication, and Javanese preserves regional identity and historical continuity. These naming practices demonstrate that pesantren signboards function not only as markers of institutional presence but also as sites where cultural heritage, religious meanings, and social aspirations intersect and evolve.